Addressing the implementation gap in advanced therapeutics for spinal muscular atrophy in the era of newborn screening programs - Leon-Astudillo, Carmen; Byrne, Barry J.; Salloum, Ramzi G. (Frontiers in Neurology, 2022)
Spinal muscular atrophy (SMA) is a rare genetic disease that results in progressive neuromuscular weakness. Without therapy, the most common form of the disease, type 1, typically results in death or chronic respiratory failure in the first two years of life. Thanks to the recent introduction of newborn screening programs and the discovery of three disease-modifying therapies in the last decade, the outcomes of children with SMA have dramatically improved. Patients are able to achieve many, if not all, of the typical neuromotor milestones, such as sitting, standing and walking, as well as safe oral intake. As the natural history of treated patients is continuously evolving, children with SMA continue to require complex and multidisciplinary care, posing implementation and sustainability challenges. Accordingly, there is a significant need for the application and evaluation of implementation science to address the steps involved in the diagnosis and treatment of patients with SMA, ensuring that all pertinent stakeholders and systems are working effectively to deliver timely and appropriate care. In this manuscript, we discuss the current challenges and gaps in the care for children with SMA, as well as how implementation science can advance this field. In addition, we provide an adapted implementation science framework that includes the main domains and subdomains involved in the care of patients with SMA.